Accurate calorie counting algorithm for carefuly plated dishes - Woon, Zheng Li (2020)
Calorie tracking technology has taken great strides in a health-oriented society. Sophisticated calorie counters employs artificial intelligence (A.I.) for pervasive and accurate calorie estimation. The general consensus in this domain is to strive for general purpose algorithm which aims to support for more variants of food and cuisine types’ recognition. These state of the art methods are tuned for accurate food recognition but do not address for accurate food portion detection. In this project, an accurate calorie counter is design to consider the amount of ingredients used in a non-occlusive plated environment. The intuition is that food ingredients; despite their underlying calories values; would further contribute significantly and differently to overall calories when varying sizes, slices, portion, pieces or units of the ingredients are used. The outcome of the project is a portion-aware calorie counter that accurately estimate the calorie on a plate depending on the amount of food served.